THE INTERRELATION BETWEEN COGNITIVE PROCESSES AND CHILDREN'S INTELLIGENCE (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article emphasizes the development of intelligence in conjunction with cognitive processes, highlighting that every child possesses an intellectual inclination toward a specific type of knowledge or activity.